CLASSIFICATION OF PERSONALITY AND EMOTIONAL INTELLIGENCE ON PROFESSIONALS WITHIN THE FIELD OF CONSTRUCTION IN BANDUNG (Malaysian Journal of Civil Engineering, 2018)
Construction project has unique characteristics. The success of the project can be measured by the effective target achievement. In construction, human resource is one of the important factors. By identifying and acknowledging the types of personality and emotional intelligence of a team of professionals within the construction field, it is expected to develop and maximize the expertise of the project team in order to achieve the success of the construction project. An interesting factor to research is the proportion type of personality and emotional intelligence of construction professionals based on the work experience and the position level within the contractor management team. This study was conducted by questionnaire to the respondents who are professionals in the construction field in the city of Bandung. Based on the result of the analysis, it seems that the level of experience and position have a considerate influence in shaping the type of personality and emotional intelligence. Professionals with experience under five years and beginner level positions tend to be ambitious, creative, always trying something new,and higly motivated in his work. As they gain experience and level positions, the mentioned characteristics changes to be someone with high leadership skills, good self-management skills, and also skillfull in managing relationship with others.